Exploring the Meaning Behind Social Stigma Towards Mental Disorders in Javanese Culture - Ningrum, Lilis Setiawati Ratna; Rahmatulloh, Ainurizan Ridho (Syntax Literate, 2026)
The social stigma surrounding mental disorders in Javanese culture is a major barrier preventing sufferers from accessing professional healthcare services. This study aims to explore the deeper meaning behind this stigma and examine the process by which it forms within the values of Javanese society. The research method used was qualitative, employing a phenomenological approach. Participants consisted of three Javanese individuals living in a Javanese cultural environment, selected using purposeful sampling with specific criteria (criterion sampling). Data analysis was conducted systematically using thematic analysis. The results indicate that the meaning of stigma in Javanese culture is deeply rooted in mystical and spiritual interpretations, where mental disorders are considered the result of supernatural interference, karma, or lack of worship. Stigma is formed through a process involving family neglect, cultural assessments of abnormality, and a lack of medical understanding, leading to negative labeling such as bento or gendeng (terms used to describe someone as mentally unwell) and acts of discrimination. This study recommends the implementation of sociocultural-based mental health interventions involving community and religious leaders. Further research should be expanded to include participants across generations to obtain a broader picture of this reality.